ANALISIS KEMAMPUAN PASSING MENGGUNAKAN KAKI BAGIAN DALAM PADA PERMAINAN FUTSAL DI SMA NEGERI 1 PANGKEP - Atifah, Nur Indah; Hasmyati, Hasmyati; Azis, Ilham; hasanuddin, M. Imran; nurulita, retno farhana; hasyim, Muhammad qasash; Nawir, Nukhrawi (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2023)
This study aims to analyze the analysis of the ability to pass with the inside of the foot in futsal games at SMA Negeri 1 Pangkep. This type of research is descriptive. The method used in this study is a survey method with data collection techniques using tests and observation sheets. The population in this study were students of class XI SMA Negeri 1 Pangkep. The sampling technique uses total sampling, so the number of samples in this study is 30 students. Data analysis uses quantitative descriptive as outlined in the form of a percentage. The results showed that the analysis of the ability to pass with the inside of the foot in futsal games at SMA Negeri 1 Pangkep was in the "very low" category of 3% (1 student), the "low" category was 20% (6 students), the "moderate" category by 27% (8 students), the "high" category was 50% (15 students), and the "very high" category was 0% (0 students). Based on the average value of 83.43, the analysis of the ability to pass with the inside of the foot in futsal games at SMA Negeri 1 Pangkep is in the "medium" category